Isolation of Saccharomyces cerevisiae TRP3. - Paluh, J L (1983)
Several plasmids, isolated from two plasmid pools, complemented a Saccharomyces cerevisiae trp3 mutant with defective indole-3-glycerol-phosphate synthase activity. Restriction mapping indicated that a 1.2-kilobase StuI segment was common to all complementing plasmids. Southern blot hybridization established that a cloned 5.2-kilobase BamHI fragment was derived intact from chromosomal DNA. A yeast trp3 mutant transformed with trp3-complementing plasmids contained approximately 40-fold elevated indole-3-glycerol-phosphate synthase activity. These plasmids also complemented an Escherichia coli trpC mutant, and transformants exhibited enzyme activity. Yeast trp3 is therefore associated with a 1.2-kilobase StuI DNA segment.